A method for preparing coal-based activated carbon for sewage treatment

By modifying the raw coal, coal-based activated carbon with high hardness, low ash content and multiple adsorption sites was prepared, which solved the problem of high ash content and low hardness in sewage treatment of existing coal-based activated carbons, and significantly improved their sewage treatment capacity.

CN118993065BActive Publication Date: 2025-03-18山东韩研活性炭有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411079082.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-07
Publication Date
2025-03-18
Estimated Expiration
2044-08-07

AI Technical Summary

Technical Problem

The existing coal-based activated carbon has high ash content, low hardness in sewage treatment, and insufficient adsorption sites, which limits its sewage treatment capacity.

Method used

Coal activated carbon with high hardness, low ash and multiple adsorption sites is prepared by modifying the treatment of raw coal, including heat treatment, crushing, batching, carbonization, activation and post-treatment.

Benefits of technology

It improves the hardness and adsorption performance of coal-based activated carbon, enhances its sewage treatment capacity, and can effectively remove organic and inorganic pollutants in the water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004983202990000131
    Figure BDA0004983202990000131
  • Figure BDA0004983202990000141
    Figure BDA0004983202990000141
  • Figure BDA0004983202990000142
    Figure BDA0004983202990000142
Patent Text Reader

Abstract

The present invention relates to a method for preparing coal-based activated carbon for sewage treatment, and belongs to the technical field of activated carbon preparation. The method comprises the following steps: S11, raw material pretreatment; S12, batching; S13, carbonization; S14, activation; S15, post-treatment; S16, modification treatment. In the present invention, a coal-based activated carbon that can be used for sewage treatment is prepared by optimizing the preparation process of coal-based activated carbon and modifying the coal-based activated carbon. By modifying the binder and modifying the activated carbon in the preparation process, the hardness of the coal-based activated carbon is increased, the ash content is reduced, and the activated carbon has more adsorption sites, thereby showing excellent sewage treatment ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of activated carbon preparation, and relates to a method for preparing coal-based activated carbon for sewage treatment. Background Art

[0002] Activated carbon is a functional carbon material with the characteristics of special microcrystalline structure, developed pores and large specific surface area. As an excellent adsorbent, it can remove organic pollutants and certain inorganic substances in water bodies and is widely used in sewage treatment.

[0003] According to the different raw materials, activated carbon can be divided into wood activated carbon, coal-based activated carbon, synthetic activated carbon and other types of activated carbon. Coal-based activated carbon is further divided into crushed activated carbon, columnar activated carbon and briquette activated carbon, among which briquette activated carbon has low floating rate and good adsorption performance, and is suitable for liquid phase fields such as water treatment. At present, the briquette activated carbon has good formability and porosity, but the ash content is high, and the requirements for raw coal production are also high, requiring low ash content and suitable adhesion. At present, the viscosity can be adjusted by weakly sticky coal or fat coal, but the reserves of weakly sticky coal are very limited, and the addition of fat coal will increase the activation time and complicate carbonization; therefore, most coal powder molding technologies still need to add various binders such as coal tar. Commonly used binders such as coal tar and coal tar will melt and volatilize after heating, making the strength of the final product not high, which is not conducive to improving the quality of activated carbon.

[0004] It is known from the prior art that the production of low-ash coal-based activated carbon by chemical activation requires that the raw coal has a low ash content, that is, the ash content is less than 12wt% or 6wt%. As the quality of coal continues to deteriorate and the ash content continues to increase, the raw coal available for use will become very limited.

[0005] Therefore, it is necessary to develop a new method for preparing coal-based activated carbon that can be used for sewage treatment. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing coal-based activated carbon for sewage treatment. The prepared coal-based activated carbon has high hardness, low ash content, more adsorption sites, and excellent sewage treatment capacity.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A method for preparing coal-based activated carbon for sewage treatment, wherein the coal-based activated carbon is subjected to modification treatment, comprising the following steps:

[0009] S11. Raw coal pretreatment:

[0010] The non-sticky coal, long flame coal and anthracite are heat treated with hot air at 130-170°C for 0.5-1h, cooled naturally to room temperature and then pulverized respectively, so that the particle size of the non-sticky coal and long flame coal is 300-400 mesh, and the particle size of the anthracite is 350-450 mesh;

[0011] S12. Ingredients:

[0012] The non-sticky coal, long flame coal and anthracite treated in step S1 are mixed in a mass ratio of 8:(1-3):(2-3), and mixed evenly by mechanical stirring at a speed of 1000-1300 r / min to obtain a mixed coal material, and then a modified epoxy resin binder of 2-4% by mass of the mixed coal material is added, and the stirring is continued at a speed of keeping uniform, and then added to a molding device, and a molding material is obtained by extrusion molding;

[0013] S13. Carbonization:

[0014] Under a nitrogen protective atmosphere, the molding material is heat-baked at 350-450°C for 2-4 hours, and then the temperature is further raised to 600-700°C at a heating rate of 2°C / min and heat-baked for 3-4 hours to obtain a calcined product, and the calcined product is acid-washed with an acid solution and then washed with deionized water to obtain a carbonized product;

[0015] S14, Activation:

[0016] The carbonized product is dried by a drying device, and the carbonized product after drying is activated by a steam activation method to obtain an activated solid, the activation temperature is controlled at 900-950°C, the activation time is controlled at 6-8h, and the amount of the activator is 1.0-1.5mL / (100g·min);

[0017] S15, post-processing:

[0018] The activated solid was added to a mixed solution of sodium hydroxide and sodium hexametaphosphate in a mass ratio of 1:1, the solid-liquid ratio of the activated solid to the mixed solution was 10: (60-100) g / mL, stirred at 75°C for 3 hours, filtered, washed with water, dried, and crushed;

[0019] S16, modification treatment:

[0020] The activated solid obtained in step S15 and the vermiculite powder are dispersed in an ethanol solution of lauric acid with a mass fraction of 15% at a solid-liquid ratio of 5:30 g / mL, respectively, and ultrasonically treated for 1 to 1.5 hours. The pretreated activated carbon and the pretreated vermiculite powder are obtained by filtering, washing with water, and drying.

[0021] In parts by weight, 15 to 20 parts of pretreated activated carbon, 6 to 8 parts of blue algae powder and 6 to 8 parts of pretreated vermiculite powder are ground by a ball mill at a speed of 400 r / min for 3 to 4 hours to obtain a mixture, the mixture is dispersed in 70 to 80 parts of deionized water, and 15 to 20 parts of sodium alginate are added, stirred at a temperature of 80 to 90° C. for 3 to 4 hours, and the temperature is continuously raised to 100 to 110° C. and stirred until the water is completely evaporated, and the mixture is crushed and passed through a 200-mesh sieve to prepare the coal-based activated carbon for sewage treatment.

[0022] As a preferred technical solution of the present invention, in step S11, the ash content of the non-caking coal, long flame coal and anthracite is 25-35wt%.

[0023] As a preferred technical solution of the present invention, in step S12, the preparation process of the modified epoxy resin binder is as follows:

[0024] S31. In parts by mass, under nitrogen, add 2 to 4 parts of citric acid and 2 to 4 parts of tartaric acid to 60 to 80 parts of water and stir well, then add 10 to 15 parts of nanocellulose, adjust the pH of the solution to 5 to 6, mix and stir for 8 to 10 hours, dry by blast drying at 100° C. for 12 hours, and then dry in a vacuum drying oven at 70° C. for 10 to 15 hours, crush the solid, and pass through a 100 to 200 mesh sieve to obtain pretreated nanocellulose;

[0025] S32, 5-10 parts of sodium lignin sulfonate and 80-95 parts of deionized water are fully mixed, the temperature is raised to 70-77° C. and stirred for 1 hour, 10-15 parts of montmorillonite are added, stirring is continued for 8-11 hours, 10-13 parts of pretreated nanocellulose are added, the temperature is continued to be raised to 105-110° C. to completely evaporate the water, and then vacuum dried at 80° C. for 8-10 hours, the obtained solid is ball-milled, and passed through a 200-mesh sieve to obtain a filler;

[0026] S33, fully and uniformly mixing 20 to 25 parts of waterborne epoxy resin, 10 to 15 parts of filler, 3 to 8 parts of curing agent and 0.5 to 2 parts of dispersant to prepare the modified epoxy resin adhesive.

[0027] As a preferred technical solution of the present invention, in step S12, the pressure during the extrusion molding is 26-28 MPa, and the compression ratio is 2-2.5.

[0028] As a preferred technical solution of the present invention, in step S13, the acid solution is one of hydrochloric acid, nitric acid and sulfuric acid solutions with a mass fraction of 15-23%.

[0029] As a preferred technical solution of the present invention, in step S15, the mass fraction of the mixed aqueous solution of sodium hydroxide and sodium hexametaphosphate is 15-20%.

[0030] As a preferred technical solution of the present invention, in step S32, the rotation speed during ball milling is 300 r / min, and the ball milling time is 3 to 5 h.

[0031] As a preferred technical solution of the present invention, in step S33, the curing agent is one of diethylenetriamine and triethylenetetramine.

[0032] As a preferred technical solution of the present invention, in step S33, the dispersant is one of potassium polyacrylate, sodium polycarboxylate and sodium polyacrylate.

[0033] In the present invention, the bonding property between activated carbon particles is improved by preparing a modified epoxy resin binder. Nanocellulose is first subjected to acid treatment in a mixed solution of citric acid and tartaric acid, so that groups such as carboxyl groups can be introduced into the surface of the nanocellulose, thereby increasing the charge number and hydrophilicity of the surface of the nanocellulose, which is beneficial to the stability of the nanocellulose. At the same time, the long chain structure of the nanocellulose is broken by hydrolysis, so that the nanocellulose has a larger specific surface area. Sodium lignin sulfonate has strong dispersibility and can be adsorbed on the surface of montmorillonite after being uniformly mixed with montmorillonite in an aqueous solution. In addition, the bonding property of sodium lignin sulfonate can help further enhance the bonding force between montmorillonite and nanocellulose, so as to form a more compact structure.

[0034] After the nanocellulose is mixed with montmorillonite, the carboxylated nanocellulose can form a network structure in the montmorillonite. At the same time, the carboxyl groups on the surface of the nanocellulose can effectively disperse the montmorillonite flakes through hydrogen bonds / electrostatic repulsion, prevent agglomeration, promote the orderly stacking of the montmorillonite, and form a denser structure. It helps to enhance the interfacial bonding force between the montmorillonite filler and the epoxy resin through the interaction force when the filler is mixed with the water-based epoxy resin to prepare the binder, thereby improving the bonding of the binder and making the activated carbon particles more tightly bonded, thereby improving the hardness of the coal-based activated carbon; and the nanocellulose on the surface of the montmorillonite can more effectively fill the micropores and defects in the water-based epoxy resin, reduce stress concentration points, and further improve the interfacial bonding force between the filler and the epoxy resin; at the same time, due to the introduction of sodium lignin sulfonate, the molecular structure contains flexible aromatic rings, which can enhance the toughness of the epoxy resin binder, thereby improving the mechanical strength.

[0035] In the present invention, coal-based activated carbon is prepared by raw material pretreatment, batching, carbonization, activation, post-treatment and activation treatment. In the carbonization process, it is first roasted at 350-450°C to remove moisture and volatiles in the raw materials, thereby reducing impurities in the raw materials and improving the purity of the carbonized product; then the temperature is raised to 600-700°C to further pyrolyze the organic components in the raw materials to generate a coke structure with a porous structure; by roasting in stages, the shape of the activated carbon can be fixed, the mechanical strength and density of the activated carbon can be improved, and the pore structure can be optimized. The carbonized product is activated by water vapor, which can effectively open and expand the pore structure of the carbon material, significantly increase the specific surface area and porosity of the activated carbon, and thus improve the adsorption of the coal-based activated carbon.

[0036] Activated carbon is treated with a mixed solution of sodium hydroxide and sodium hexametaphosphate. The surface of the activated carbon is cleaned by the action of alkali, reducing the impact of impurities and pollutants on its adsorption performance. Sodium hexametaphosphate can help remove or stabilize impurities in the solution through chelation, thereby indirectly improving the surface environment of the activated carbon, making the pore structure of the activated carbon more open and unobstructed, increasing the adsorption sites of the activated carbon, and further improving its adsorption performance.

[0037] In the present invention, activated carbon and vermiculite powder are firstly pretreated by lauric acid, and functional groups such as carboxyl groups in the molecular structure of lauric acid can react with functional groups on the surface of activated carbon, thereby changing the surface chemical properties of activated carbon and improving its adsorption. Vermiculite powder is a natural silicate mineral, and through acid treatment, the surface area and roughness of vermiculite can be increased, the surface charge can be changed, and the treatment of heavy metal ions in water by ion exchange of vermiculite can be enhanced. The surface areas of vermiculite powder and activated carbon treated with acid are increased, and the blue algae powder is fully mixed with blue algae powder through ball milling, so that the blue algae powder can be uniformly loaded on the porous structure of vermiculite and activated carbon. The blue algae powder has certain biological activity, and the amino groups, amide bonds and carbonyl groups on the surface can be complexed, ion exchanged and electrostatically attracted with heavy metal ions in water, thereby further increasing the adsorption capacity of activated carbon. With the assistance of vermiculite powder and cyanobacteria powder, it helps to reduce the content of organic matter in water, thereby reducing the adsorption load of activated carbon and indirectly improving the sewage treatment effect of activated carbon; then the surface is coated with sodium alginate. Sodium alginate can be used as a suitable fixed matrix to coat the surface of modified activated carbon to form a protective film. This coating can improve the adsorption performance. After mixing with activated carbon with cyanobacteria powder loaded on the surface and vermiculite powder, a synergistic adsorption effect can be formed to increase the adsorption sites on the surface of the mixture and enhance the overall adsorption capacity. The molecular chain of sodium alginate contains a large number of functional groups such as hydroxyl and carboxyl groups. These functional groups can chemically react or physically adsorb with pollutants in water, thereby improving the adsorption efficiency of the mixture; at the same time, this coating effect improves the dispersion and stability of the mixture in water, prevents it from agglomerating or precipitating during use, thereby improving the separation effect.

[0038] Beneficial effects of the present invention:

[0039] In the present invention, a coal-based activated carbon that can be used for sewage treatment is prepared by optimizing the preparation process of coal-based activated carbon and modifying the coal-based activated carbon. By modifying the binder and modifying the activated carbon during the preparation process, the hardness of the coal-based activated carbon is increased, the ash content is reduced, and it has more adsorption sites, thereby showing excellent sewage treatment ability in sewage treatment. DETAILED DESCRIPTION

[0040] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0041] In the following examples and comparative examples:

[0042] The ash content of non-caking coal, long flame coal and anthracite is 25-35wt%.

[0043] Vermiculite: purchased from Shijiazhuang Leitai Technology Co., Ltd., and obtained by crushing vermiculite powder;

[0044] Cyanobacteria powder: purchased from Fufeng Snotech Biotechnology Co., Ltd.

[0045] Sodium alginate: purchased from Wuhan Jiyesheng Chemical Co., Ltd.;

[0046] Lauric acid: purchased from Shanghai Shengyue International Trade Co., Ltd.

[0047] Citric acid: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: C792205;

[0048] Tartaric acid: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: D875395;

[0049] Nanocellulose: purchased from Guangzhou Yingsheng Biotechnology Co., Ltd.

[0050] Sodium lignin sulfonate: purchased from Shandong Yonglida New Materials Technology Co., Ltd., product number: YLD-YH02;

[0051] Montmorillonite: purchased from Hubei Hengjingrui Chemical Co., Ltd.

[0052] Water-based epoxy resin: purchased from Wuhan Penglei Biotechnology Co., Ltd.;

[0053] Diethylenetriamine: purchased from Jinan Chuangshi Chemical Co., Ltd.

[0054] Sodium polyacrylate: purchased from Hubei Zhonglong Kangsheng Fine Chemical Co., Ltd.;

[0055] Sodium hydroxide: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: S822411;

[0056] Sodium hexametaphosphate: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: S817848.

[0057] Example 1

[0058] S11. Raw coal pretreatment:

[0059] The non-sticky coal, long flame coal and anthracite were heat treated with hot air at 130°C for 0.5h, cooled naturally to room temperature and then pulverized respectively, so that the particle size of the non-sticky coal and long flame coal was 300 mesh, and the particle size of the anthracite was 350 mesh;

[0060] S12. Ingredients:

[0061] The non-sticky coal, long flame coal and anthracite treated in step S1 are mixed in a mass ratio of 8:1:2, and mixed evenly by mechanical stirring at a speed of 1000r / min to obtain a mixed coal material, and then a modified epoxy resin binder of 2% by mass of the mixed coal material is added, and the stirring is continued at a speed of 1000r / min, and then added to a molding device, and a molding material is obtained by extrusion molding, and the pressure during extrusion molding is 26MPa, and the compression ratio is 2;

[0062] Preparation of modified epoxy resin adhesive:

[0063] In parts by mass, under nitrogen, 2 parts of citric acid and 2 parts of tartaric acid were added to 60 parts of water and stirred thoroughly, and then 10 parts of nanocellulose were added, the pH of the solution was adjusted to 5, mixed and stirred for 8 hours, and dried by blast drying at 100° C. for 12 hours and then dried in a vacuum drying oven at 70° C. for 10 hours, and the solid was crushed and passed through a 100-mesh sieve to obtain pretreated nanocellulose;

[0064] 5 parts of sodium lignin sulfonate and 80 parts of deionized water were fully mixed, heated to 70°C and stirred for 1 hour, then 10 parts of montmorillonite were added, and the stirring was continued for 8 hours, and then 10 parts of pretreated nanocellulose were added, and the temperature was continued to be raised to 105°C to completely evaporate the water, and then vacuum dried at 80°C for 8 hours, and the obtained solid was ball-milled at a speed of 300 r / min for 3 hours and passed through a 200-mesh sieve to obtain a filler;

[0065] 20 parts of waterborne epoxy resin, 10 parts of filler, 3 parts of diethylenetriamine and 0.5 parts of sodium polyacrylate were fully stirred to prepare a modified epoxy resin adhesive.

[0066] S13. Carbonization:

[0067] Under a nitrogen protective atmosphere, the molding material was calcined at 350°C for 2 hours, and then the temperature was further increased to 600°C at a heating rate of 2°C / min and pyrolyzed for 3 hours to obtain a calcined product. The calcined product was pickled with a sulfuric acid solution with a mass fraction of 15%, and then washed with deionized water to obtain a carbonized product.

[0068] S14, Activation:

[0069] The carbonized product was dried by a drying device, and the carbonized product after drying was activated by a steam activation method to obtain an activated solid. The activation temperature was controlled at 900°C, the activation time was controlled at 6h, and the amount of the activator was 1.0mL / (100g·min);

[0070] S15, post-processing:

[0071] The activated solid was added to a mixed solution of sodium hydroxide and sodium hexametaphosphate in a mass ratio of 1:1 with a mass fraction of 15%, and the solid-liquid ratio of the activated solid to the mixed solution was 10:60 g / mL, stirred at 75°C for 3 hours, filtered, washed with water, dried, and crushed;

[0072] S16, modification treatment:

[0073] The activated solid obtained through step S15 and the vermiculite powder were dispersed in an ethanol solution of lauric acid with a mass fraction of 15% at a solid-liquid ratio of 5:30 g / mL, respectively, and ultrasonically treated for 1 h. The pretreated activated carbon and the pretreated vermiculite powder were obtained by filtering, washing with water, and drying.

[0074] In parts by weight, 15 parts of pretreated activated carbon, 6 parts of cyanobacteria powder and 6 parts of pretreated vermiculite powder are ground by a ball mill at a speed of 400 r / min for 3 hours to obtain a mixture, the mixture is dispersed in 70 parts of deionized water, and 15 parts of sodium alginate are added, stirred at a temperature of 80°C for 3 hours, and then the temperature is continuously raised to 100°C, stirred until the water is completely evaporated, crushed, and passed through a 200-mesh sieve to prepare the coal-based activated carbon for sewage treatment.

[0075] Example 2

[0076] S11. Raw coal pretreatment:

[0077] The non-sticky coal, long flame coal and anthracite were heat treated by hot air at 150°C for 0.7h, cooled naturally to room temperature and then pulverized respectively, so that the particle size of the non-sticky coal and long flame coal was 350 mesh, and the particle size of the anthracite was 400 mesh;

[0078] S12. Ingredients:

[0079] The non-sticky coal, long flame coal and anthracite treated in step S1 are mixed in a mass ratio of 8:2:2.5, and mixed evenly by mechanical stirring at a speed of 1100r / min to obtain a mixed coal material, and then a modified epoxy resin binder of 3% by mass of the mixed coal material is added, and the stirring is continued at a speed of keeping uniform, and then added to a molding device, and a molding material is obtained by extrusion molding, and the pressure during extrusion molding is 27MPa, and the compression ratio is 2.2;

[0080] Preparation of modified epoxy resin adhesive:

[0081] In parts by mass, under nitrogen, 3 parts of citric acid and 3 parts of tartaric acid were added to 70 parts of water and stirred thoroughly, and then 13 parts of nanocellulose were added, and the pH value of the solution was adjusted to 5, and the mixture was mixed and stirred for 9 hours, and then dried at 100° C. for 12 hours and then dried in a vacuum drying oven at 70° C. for 12 hours, and the solid was crushed and passed through a 150-mesh sieve to obtain pretreated nanocellulose;

[0082] 8 parts of sodium lignin sulfonate and 88 parts of deionized water were fully mixed, heated to 74°C and stirred for 1 hour, then 13 parts of montmorillonite were added, and the stirring was continued for 9 hours, and then 12 parts of pretreated nanocellulose were added, and the temperature was continued to be raised to 107°C to completely evaporate the water, and then vacuum dried at 80°C for 9 hours, and the obtained solid was ball-milled at a speed of 300 r / min for 4 hours and passed through a 200-mesh sieve to obtain a filler;

[0083] 22 parts of waterborne epoxy resin, 13 parts of filler, 5 parts of diethylenetriamine and 2 parts of sodium polyacrylate were fully stirred to prepare a modified epoxy resin adhesive.

[0084] S13. Carbonization:

[0085] Under a nitrogen protective atmosphere, the molding material was calcined at 400°C for 3 hours, and then heated to 650°C at a heating rate of 2°C / min and pyrolyzed for 3.5 hours to obtain a calcined product. The calcined product was acid-washed with a sulfuric acid solution with a mass fraction of 18%, and then washed with deionized water to obtain a carbonized product.

[0086] S14, Activation:

[0087] The carbonized product was dried by a drying device, and the carbonized product after drying was activated by a steam activation method to obtain an activated solid. The activation temperature was controlled at 920°C, the activation time was controlled at 7h, and the amount of the activator was 1.2mL / (100g·min);

[0088] S15, post-processing:

[0089] The activated solid was added to a mixed solution of sodium hydroxide and sodium hexametaphosphate in a mass ratio of 1:1 with a mass fraction of 17%, and the solid-liquid ratio of the activated solid to the mixed solution was 10:80 g / mL, stirred at 75°C for 3 hours, filtered, washed with water, dried, and crushed;

[0090] S16, modification treatment:

[0091] The activated solid obtained through step S15 and the vermiculite powder were dispersed in an ethanol solution of lauric acid with a mass fraction of 15% at a solid-liquid ratio of 5:30 g / mL, respectively, and ultrasonically treated for 1.3 h. The pretreated activated carbon and the pretreated vermiculite powder were obtained by filtering, washing with water, and drying.

[0092] In parts by weight, 18 parts of pretreated activated carbon, 7 parts of cyanobacteria powder and 7 parts of pretreated vermiculite powder are ground by a ball mill at a speed of 400 r / min for 3.5 hours to obtain a mixture, the mixture is dispersed in 75 parts of deionized water, and 16 parts of sodium alginate are added, stirred at a temperature of 85°C for 3.5 hours, and the temperature is continuously raised to 105°C, stirred until the water is completely evaporated, crushed, and passed through a 200-mesh sieve to prepare the coal-based activated carbon for sewage treatment.

[0093] Example 3

[0094] S11. Raw coal pretreatment:

[0095] The non-sticky coal, long flame coal and anthracite were heat treated with hot air at 170°C for 1 hour, cooled naturally to room temperature and then pulverized respectively, so that the particle size of the non-sticky coal and long flame coal was 400 mesh, and the particle size of the anthracite was 450 mesh;

[0096] S12. Ingredients:

[0097] The non-sticky coal, long flame coal and anthracite treated in step S1 are mixed in a mass ratio of 8:3:3, and mixed evenly by mechanical stirring at a speed of 1300r / min to obtain a mixed coal material, and then a modified epoxy resin binder of 4% by mass of the mixed coal material is added, and the stirring is continued at a speed of 1300r / min, and then added to a molding device, and a molding material is obtained by extrusion molding, and the pressure during extrusion molding is 28MPa, and the compression ratio is 2.5;

[0098] Preparation of modified epoxy resin adhesive:

[0099] In parts by mass, under nitrogen, 4 parts of citric acid and 4 parts of tartaric acid were added to 80 parts of water and stirred thoroughly, and then 15 parts of nanocellulose were added, and the pH value of the solution was adjusted to 6, and the mixture was mixed and stirred for 10 hours, and then dried by blast drying at 100° C. for 12 hours and then dried in a vacuum drying oven at 70° C. for 15 hours, and the solid was crushed and passed through a 200-mesh sieve to obtain pretreated nanocellulose;

[0100] 10 parts of sodium lignin sulfonate and 95 parts of deionized water were fully mixed, heated to 77°C and stirred for 1 hour, 15 parts of montmorillonite were added, and the stirring was continued for 11 hours, and 13 parts of pretreated nanocellulose were added, and the temperature was continued to be raised to 110°C to completely evaporate the water, and then vacuum dried at 80°C for 10 hours, and the obtained solid was ball-milled at a speed of 300 r / min for 5 hours and passed through a 200-mesh sieve to obtain a filler;

[0101] 25 parts of waterborne epoxy resin, 15 parts of filler, 8 parts of diethylenetriamine and 0.5-2 parts of sodium polyacrylate were fully stirred to prepare a modified epoxy resin adhesive.

[0102] S13. Carbonization:

[0103] Under a nitrogen protective atmosphere, the molding material was calcined at 450°C for 4 hours, and then the temperature was further increased to 700°C at a heating rate of 2°C / min and pyrolyzed for 4 hours to obtain a calcined product. The calcined product was pickled with a hydrochloric acid solution with a mass fraction of 23%, and then washed with deionized water to obtain a carbonized product.

[0104] S14, Activation:

[0105] The carbonized product was dried by a drying device, and the carbonized product after drying was activated by a steam activation method to obtain an activated solid. The activation temperature was controlled at 950°C, the activation time was controlled at 8h, and the amount of the activator was 1.5mL / (100g·min);

[0106] S15, post-processing:

[0107] The activated solid was added to a mixed solution of sodium hydroxide and sodium hexametaphosphate in a mass ratio of 1:1 with a mass fraction of 20%, and the solid-liquid ratio of the activated solid to the mixed solution was 10:100 g / mL, stirred at 75°C for 3 hours, filtered, washed with water, dried, and crushed;

[0108] S16, modification treatment:

[0109] The activated solid obtained through step S15 and the vermiculite powder were dispersed in an ethanol solution of lauric acid with a mass fraction of 15% at a solid-liquid ratio of 5:30 g / mL, respectively, and ultrasonically treated for 1.5 h. The pretreated activated carbon and the pretreated vermiculite powder were obtained by filtering, washing with water, and drying.

[0110] In parts by weight, 20 parts of pretreated activated carbon, 8 parts of cyanobacteria powder and 8 parts of pretreated vermiculite powder are ground by a ball mill at a speed of 400 r / min for 4 hours to obtain a mixture, the mixture is dispersed in 80 parts of deionized water, and 20 parts of sodium alginate are added, stirred at a temperature of 90°C for 4 hours, and the temperature is continuously raised to 110°C, stirred until the water is completely evaporated, crushed, and passed through a 200-mesh sieve to prepare the coal-based activated carbon for sewage treatment.

[0111] Comparative Example 1

[0112] The difference between Comparative Example 1 and Example 1 is that the nanocellulose is not pretreated when preparing the modified epoxy resin binder in Comparative Example 1, and the other operations are the same.

[0113] Comparative Example 2

[0114] The difference between Comparative Example 2 and Example 1 is that sodium lignin sulfonate is not added when preparing the modified epoxy resin binder in Comparative Example 2, and the other operations are the same.

[0115] Comparative Example 3

[0116] The difference between Comparative Example 3 and Example 1 is that the activated carbon and vermiculite powder in the modification step in Comparative Example 3 are not pretreated, and the other operations are the same.

[0117] Comparative Example 4

[0118] The difference between Comparative Example 4 and Example 1 is that no cyanobacteria powder is added in the modification step in Comparative Example 4, and the other operations are the same.

[0119] Comparative Example 5

[0120] The difference between Comparative Example 5 and Example 1 is that sodium alginate is not added in the modification step in Comparative Example 5, and the other operations are the same.

[0121] Performance Test:

[0122] 1. The basic properties of the coal-based activated carbon prepared in the examples and comparative examples were tested, and the results are shown in Table 1: The ash content is based on the standard: GB / T 7702.15-2008, the mechanical strength is based on the standard: GB / T7702.3-2008; the specific surface area is based on the standard: GB / T7702.20-2008; the ball-disc hardness is based on the standard ASTM;

[0123] Table 1

[0124]

[0125]

[0126] 2. Sewage treatment capacity:

[0127] 2.1. COD removal rate and total nitrogen removal rate are determined by the following method:

[0128] The coal-based activated carbon prepared by the embodiment and the comparative example was placed in water, allowed to stand for 30 minutes, filtered, and then placed in sewage, stirred for 10 minutes, allowed to stand for 20 minutes, and the stirring and standing treatments were repeated 5 times, and filtered to obtain a treated water sample. The COD content and total nitrogen content of the treated water sample were detected, and the COD removal rate and total nitrogen removal rate of the sample were calculated. The initial COD content of the sewage was 100 mg / L, and the total nitrogen content was 25 mg / L. The weight ratio of the sample to the sewage was 1:1000;

[0129] 2.2. Taking heavy metal lead as an example, weigh 300 mg of lead nitrate and dissolve it in 1 L of water to prepare Pb 2+The initial ion concentration of the heavy metal wastewater simulation solution was 300 mg / L. 5 g of the coal-based activated carbon prepared in the embodiment and the comparative example were added to 100 mL of the heavy metal wastewater simulation solution and stirred for adsorption for 35 min. The specific test results are shown in the following two tables:

[0130] Table 2

[0131]

[0132]

[0133] According to the above data, the coal-based activated carbon prepared in the present invention has low ash content, high hardness, and good adsorption effect, and can be used for sewage treatment.

[0134] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing coal-based activated carbon for sewage treatment, characterized in that: The coal-based activated carbon is modified, comprising the following steps: S11, Raw coal pretreatment: The non-sticky coal, long flame coal and anthracite are heat treated with hot air at 130-170°C for 0.5-1h, cooled naturally to room temperature and then pulverized respectively, so that the particle size of the non-sticky coal and long flame coal is 300-400 mesh, and the particle size of the anthracite is 350-450 mesh; S12. Ingredients: The non-sticky coal, long flame coal and anthracite treated in step S1 are mixed in a mass ratio of 8:(1-3):(2-3), and mixed evenly by mechanical stirring at a speed of 1000-1300 r / min to obtain a mixed coal material, and then a modified epoxy resin binder of 2-4% by mass of the mixed coal material is added, and the stirring is continued at a speed of keeping uniform, and then added to a molding device, and a molding material is obtained by extrusion molding; S13. Carbonization: Under a nitrogen protective atmosphere, the molding material is heat-baked at 350-450°C for 2-4 hours, and then the temperature is further raised to 600-700°C at a heating rate of 2°C / min and heat-baked for 3-4 hours to obtain a calcined product, and the calcined product is acid-washed with an acid solution and then washed with deionized water to obtain a carbonized product; S14, Activation: The carbonized product is dried by a drying device, and the carbonized product after drying is activated by a steam activation method to obtain an activated solid, the activation temperature is controlled at 900-950°C, the activation time is controlled at 6-8h, and the amount of the activator is 1.0-1.5mL / (100g·min); S15, post-processing: The activated solid was added to a mixed solution of sodium hydroxide and sodium hexametaphosphate in a mass ratio of 1:1, the solid-liquid ratio of the activated solid to the mixed solution was 10: (60-100) g / mL, stirred at 75°C for 3 hours, filtered, washed with water, dried, and crushed; S16, modification treatment: The activated solid obtained in step S15 and the vermiculite powder are dispersed in an ethanol solution of lauric acid with a mass fraction of 15% at a solid-liquid ratio of 5:30 g / mL, respectively, and ultrasonically treated for 1 to 1.5 hours. The pretreated activated carbon and the pretreated vermiculite powder are obtained by filtering, washing with water, and drying. In parts by weight, 15 to 20 parts of pretreated activated carbon, 6 to 8 parts of blue algae powder and 6 to 8 parts of pretreated vermiculite powder are ground by a ball mill at a speed of 400 r / min for 3 to 4 hours to obtain a mixture, the mixture is dispersed in 70 to 80 parts of deionized water, and 15 to 20 parts of sodium alginate are added, stirred at a temperature of 80 to 90° C. for 3 to 4 hours, and the temperature is continuously raised to 100 to 110° C. and stirred until the water is completely evaporated, and the mixture is crushed and passed through a 200-mesh sieve to prepare the coal-based activated carbon for sewage treatment.

2. The method for preparing coal-based activated carbon for sewage treatment according to claim 1, characterized in that: In step S11, the ash content of the non-caking coal, long flame coal and anthracite is 25-35wt%.

3. The method for preparing coal-based activated carbon for sewage treatment according to claim 1, characterized in that: In step S12, the preparation process of the modified epoxy resin adhesive is as follows: S31. In parts by mass, under nitrogen, add 2 to 4 parts of citric acid and 2 to 4 parts of tartaric acid to 60 to 80 parts of water and stir well, then add 10 to 15 parts of nanocellulose, adjust the pH of the solution to 5 to 6, mix and stir for 8 to 10 hours, dry by blast drying at 100° C. for 12 hours, and then dry in a vacuum drying oven at 70° C. for 10 to 15 hours, crush the solid, and pass through a 100 to 200 mesh sieve to obtain pretreated nanocellulose; S32, 5-10 parts of sodium lignin sulfonate and 80-95 parts of deionized water are fully mixed, the temperature is raised to 70-77° C. and stirred for 1 hour, 10-15 parts of montmorillonite are added, stirring is continued for 8-11 hours, 10-13 parts of pretreated nanocellulose are added, the temperature is continued to be raised to 105-110° C. to completely evaporate the water, and then vacuum dried at 80° C. for 8-10 hours, the obtained solid is ball-milled, and passed through a 200-mesh sieve to obtain a filler; S33, fully and uniformly mixing 20 to 25 parts of waterborne epoxy resin, 10 to 15 parts of filler, 3 to 8 parts of curing agent and 0.5 to 2 parts of dispersant to prepare the modified epoxy resin adhesive.

4. The method for preparing coal-based activated carbon for sewage treatment according to claim 1, characterized in that: In step S12, the pressure during the extrusion molding is 26-28 MPa, and the compression ratio is 2-2.

5.

5. The method for preparing coal-based activated carbon for sewage treatment according to claim 1, characterized in that: In step S13, the acid solution is one of hydrochloric acid, nitric acid and sulfuric acid solutions with a mass fraction of 15-23%.

6. The method for preparing coal-based activated carbon for sewage treatment according to claim 1, characterized in that: In step S15, the mass fraction of the mixed solution of sodium hydroxide and sodium hexametaphosphate is 15-20%.

7. The method for preparing coal-based activated carbon for sewage treatment according to claim 3, characterized in that: In step S32, the rotation speed during ball milling is 300 r / min, and the ball milling time is 3 to 5 hours.

8. The method for preparing coal-based activated carbon for sewage treatment according to claim 3, characterized in that: In step S33, the curing agent is one of diethylenetriamine and triethylenetetramine.

9. The method for preparing coal-based activated carbon for sewage treatment according to claim 3, characterized in that: In step S33, the dispersant is one of potassium polyacrylate, sodium polycarboxylate and sodium polyacrylate.

Citation Information

Patent Citations

  • Low-ash ultrahigh-specific area active carbon and preparation method thereof

    CN103566871A

  • Preparation method of low-ash briquetting coaly activated carbon

    CN112239206A